The Influence of Height on Self-Confidence in Students - Serva, Samuel Gerardo Putera; Ray, Algani Adam; Wati, Irma; Siregar, Ummu Habibah (Lembaga Junal dan Publikasi, Universitas Muhammadiyah Buton, 2023)
Confidence is the capital that is owned by every individual in an effort to actualize themselves, one of the factors that influence self-confidence is height. The purpose of this study was to find out whether height has an influence on self-confidence. This research method is descriptive quantitative. The population in this study were 266 students of the Communication Studies Program at Mercu Buana University, Yogyakarta, with a sample of 116 respondents using a probability sampling technique. The instruments used in this study were height indicators and self-confidence questionnaires based on Lauster's theory (2012). The data obtained were then analyzed using the Pearson’s technique. The results of the study found that most of the respondents had low self-confidence, namely 50.9% and had above average height, namely 68.1%. The results of the regression analysis obtained a significance value of 0.002 (p <0.05) and an r square of 8.1% which indicates that there is an effect of height on self-confidence. In conclusion, there is an effect of height on self-confidence of 8.1%, while 90.9% is influenced by other variables. Suggestions for future researchers are to be able to follow up on other variables that affect self-confidence.